Negative Communication on The Perspective of Indonesian Religion Ministry in Tafsir Tematik Departemen Agama: An Effort to Build Positive Attitudes and Words - Rizki Firmansyah (Universitas Ahmad Dahlan, 2023)
Many people miss understanding more deeply that Koran only talks about the lawful and unlawful, the reward for sin, and heaven and hell. The Koran is a holy book that presents various general descriptions of issues in human life. In the present context, the Quran can always adapt itself, its understanding is not only limited to 1500 years ago, and the sentences in it are so rich in messages. The wealth of Quranic sentences are strung together in many existing commentary books. One of the thematic studies of the Koran is about communication and information in the Koran. Overall, the Quran is the book of God's communication with his creatures, in which it contains the creator's “talk” to humans to listen, respond, and carry out orders, human understanding of this form of Quranic communication will lead to many positive actions. One thing that may be overlooked is that positive actions do not always come from positive sentences, there are passages in the Quran which in their communications present negative sentences to turn them into positive actions. This research is a qualitative study using a text analysis approach, the main source obtained in this study comes from the thematic interpretations written by the team of the Republic of Indonesia's Department of Religion. The conclusion of this study found several verses with negative nuances mentioned in the Quran so that humans remember and stay away from them.